Non-Hodgkin’s Gastric Lymphoma: Case Report - Ghosh , Jhumur; Sami, Samia Hossain; Ghosh, Jaya (Journal for Research in Applied Sciences and Biotechnology, 2023)
More than 95% of gastric lymphomas are Non-Hodgkin’s lymphoma. It is very difficult to distinguish primary gastric lymphoma from secondary stomach dissemination. Here we reported a case of high-grade B cell type Non-Hodgkin’s gastric lymphoma. The patient presented with upper abdominal swelling associated with anorexia, vomiting, and weight loss. He was hemodynamically unstable and needed ICU support. But before starting R-CHOP chemotherapy he was expired. The diagnosis of gastric lymphoma can be delayed for many years due to the presence of nonspecific symptoms. High-grade Non-Hodgkin’s lymphoma is very aggressive, but treatment response is better than low-grade lymphoma. Here we suggest early diagnosis and management of high-grade Non-Hodgkin’s gastric lymphoma to save the patient’s life.